Traditional Law Areas Relevant To Overcoming The Problems Of The Indonesian Nation In The Globalization Era - Afnaini Afnaini; Hamdan Hamdan (Jurnal Restorasi : Hukum dan Politik, 2023)
Customary law is unwritten legal regulations that grow and develop and are maintained with the legal awareness of the community. Customary law is the law of the Indonesian people and is spread throughout Indonesia with various features and characteristics. The purpose of this research is to find out the constitutional position of the existence of customary law and the alliance of customary law communities and which two areas of customary law are still relevant in overcoming problems faced by the Indonesian nation in the era of globalization. With the normative juridical research method, it is known that the constitutionality of the existence of customary law and the association of customary law communities has a strong constitutional juridical status as stipulated in Article 18 B paragraph (2) and Article 28 I paragraph (3) of the 1945 Constitution of the Republic of Indonesia and is strengthened by the existence of juridical guarantees from several sectoral laws governing traditional rights. Areas of customary law that are still relevant in overcoming current problems include both neutral law fields such as family and inheritance law, land rights, namely ulayat, rights to gain from office, rights to withdraw the results of usage rights, and related transactions. with land such as, lease rights, split pinang (maro) agreements, leases and guarantees in transfer of rights relating to land and non-neutrality.